Phosphorus more than temperature controls the phytoplankton community in a deep quarry lake: a combined field and laboratory approach. Issue 1 (2nd January 2018) - Pannard, A.; Guislain, A.; Chorin, M.; Mahé, S.; Bouger, G.; Crave, A.; Le Rouzic, B.; Bormans, M.
Abstract: Phytoplankton community structure and their abiotic drivers are seldom studied in quarry lakes. We monitored the phytoplankton and physical and chemical conditions of a deep quarry lake for more than a year. The lake was meromictic and phosphorus concentrations remained low year-round. The phytoplankton community was dominated by a small Cosmarium species, identified by molecular techniques, which persisted throughout the year. Laboratory experiments were additionally performed to test which abiotic factors control the phytoplankton community of the lake: nutrients, water temperature, or their interaction. An increase of phosphorus alone increased biomass and changed the community structure, selecting low temperature adapted species, while higher temperature alone and increase in nitrates alone had no effect. Higher temperature associated with nutrient input increased biomass and led to a third community structure dominated by fast growing species with low sedimentation loss. Cosmarium sp. dominated treatments without phosphorus inputs at all temperatures but was easily outcompeted in phosphorus-replete conditions. The thermo-tolerance of Cosmarium sp., associated with a high affinity for phosphorus and low sinking losses, allows this species to dominate in situ year-round. Results from both in situ and laboratory experiments indicated that phosphorus exerts a stronger control than temperature on the phytoplankton community of the quarry lake during the entire year, similar to natural lakes.